A reading of archaeological and anthropological results of the second half of the 19th Century on paleoanthropological skull in a Prehistoric cave of North West Lombardy. - Badino, Paola; Licata, Marta; Martini, Mariano; Iorio, Silvia (Acta Biomedica Atenei Parmensis, 2017)
N/A